THE PROGRESIVE RECHTSVINDING IN CRIMINAL JUSTICE PROCESS - Wahyu, Wahyu (Tadulako Law Review, 2016)
The positive law still dominates in Indonesian’s law. Currently the legal institutions must do a new beginning. Legal proceedings not often able to resolve the law issue clearly, even provide the substantive justice for both of the perpetrators and the victims. The discovery of progressive law in the criminal justice process is indispensable today.  For example is to implement the progressive judge’s decision that’s mean it is not just legalistic as a depictions of the constitution, judge’s decision not only to maintain order but to deliver improvements in public and to build the social harmonitations. For the last, judge’s decision must be visionary that reborned the courage morality  and legal breakthrough for the better nation.